Effects of stocking density and diets on survival and growth of lavi-cultured slipper lobster (\(Thenus orientalis\) Lund, 1793) - Nguyen Van, Manh; Nguyen Quoc, Thang; Dao Mong, Uyen; Truong Quoc, Thai (Vietnam Journal of Marine Science and Technology, 2023)
A study on the effect of different densities and feed when rearing phyllosoma larvae of slipper lobster (Thenus Orientalis) was conducted at Nha Trang Marine Research and Development Center, Institute of Aquaculture Research No. 3 from January to April 2020 to evaluate the effect of density and types of food on survival, growth (phase transition rate, phyllosoma larval size: CL and CW). In general, the impact of feed on phyllosoma larvae was recorded in such parameters as survival rate, stage transition rate, and larval size (CL and CW). The results showed that the survival rate of phyllosoma larvae depends on the density of rearing phyllosoma larvae, and the appropriate density when breeding is 15 fish/L. However, density does not affect the growth of phyllosoma larvae. Besides, the best feed formula for rearing phyllosoma larvae in this study was umbrella Artemia + (white clam) fresh meat for the first seven days, and newly hatched Artemia + white clam meat continued to be fed from day one, 8th to 24th day.